Structural, electrical and magnetic properties of Mg-Zr co-substituted Ni0.5Zn0.5Fe2O4 - K. Jalaiah; K. Chandra Mouli; K. Vijaya Babu; R.V. Krishnaiah (Journal of Science: Advanced Materials and Devices, 2019)
Zr and Mg co-substituted Ni0.5Zn0.5Fe2O4 ferrites have been synthesized by the sol-gel auto-combustion method. The X-ray diffraction patterns evidenced the single phase cubic spinel structure. The lattice parameter and cell volume are in resemblance trend with the variation of the dopant concentration. The similar trend is observed for the crystallite and particle size. The porosity and sintered density, however, vary in an opposite way with a variation of the dopant concentration. The same variation is found for the drift mobility and DC resistivity. The Arrhenius graphs of DC resistivity exhibit the semiconductor nature, for which the activation energy decreased with increasing the dopant concentration. Moreover, as the dopant contents increased, the saturation magnetization, net magnetic moment and permeability are reduced, while the coercivity is reinforced. These findings can be correlated with the variation of the porosity and grain size. Keywords: Ferrites, XRD, TEM, SEM, Permeability, Saturation magnetization, Anisotropy constant